The future of fruit and vegetables in the food system of Tanzania: A visioning exercise - Mwombeki, Wiston; Dijkxhoorn, Youri; de Steenhuijsen Piters, Bart (CGIAR System Organization, 2024)
This report describes the results of expert and stakeholder consultations held from 10 to 13 June 2024, organized by the One CGIAR program on Fruit and Vegetables for Sustainable Healthy Diets (FRESH). The exercise aimed to explore the future role of fruits and vegetables in the Tanzanian food system. These crops are important to healthy diets and generate income for value chain actors. It is, therefore, important to understand which trends and uncertainties may shape their role in future food systems and what actors can do to steer developments in the desired direction. The report explains the approach to such foresight analysis and describes the current state of fruit and vegetables in the Tanzanian food system with a focus on the Arusha and Kilimanjaro regions. Alternative futures are explored regarding their consequences and options for anticipatory policy and stakeholder engagement.